PENGUJIAN AKARAKTERISTIK PASIR PANTAI KABUPATEN KOLAKA SEBAGAI MATERIAL ALTERNATIF PEMBUATAN BETON (Pasir Pantai Kec. Tanggetada, Kec. Watubangga dan Kec. Toari) - Muhammad Buttomi Masgode; Bagus Eko Prasetyo; Arman Hidayat; Rustan Rahman Rustan; Basri Basri (LPPM, 2024)
The quality characteristics of the concrete produced are greatly influenced by the quality of the fine aggregate used as a structural component, because fine aggregate has a large influence on the volume of concrete. So, the use of beach sand as a construction material must meet the specified requirements. The aim of this research is to determine the characteristics of beach sand in 3 (three) sub-districts in Kolaka district, whether it can be used in making concrete or not. The research method used was a detailed experiment carried out at the Concrete Laboratory of Sembilanbelas November University Kolaka with samples of Tanggetada Beach Sand, Watubangga Beach Sand and Toari Beach Sand. The results of testing the characteristics of the three beach sands used were obtained by testing data that met the requirements specified in SNI 03-1971-1990, except for the sieve analysis examination at No. 50 for all sand locations and No. 100 for Tanggetada and Toari Beach sand locations. Meanwhile, the specific gravity and water absorption, bulk weight, water content and passing sieve No. 200 have met the specifications. From the results obtained, the use of Watubangga Beach Sand can be used as sand material for normal concrete construction.